2018
DOI: 10.1088/1361-6579/aae0ea
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for intraoperative prediction of viability in ischemic small intestine

Abstract: Intraoperative bioimpedance measurements on intestine of suspect viability combined with machine learning can increase the accuracy of intraoperative assessment of intestinal viability. Increased accuracy in intraoperative assessment of intestinal viability has the potential to reduce the high mortality and morbidity rate of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The classification performance using FNN and RNN-LSTM with bioimpedance data (Strand-Amundsen et al, 2018c), to predict intestinal tissue viability and histological grading based on the reference data (Strand-Amundsen et al, 2018a) indicates that good binary prediction of tissue viability is possible based on one bioimpedance measurement before reperfusion and an FNN model. When using the whole time-course of repeated bioimpedance measurement during the experiments a significantly higher accuracy was obtained by utilizing LSTM-RNN ( Figure 29).…”
Section: Machine Learning and Bioimpedance -Results (Paper V)mentioning
confidence: 99%
See 2 more Smart Citations
“…The classification performance using FNN and RNN-LSTM with bioimpedance data (Strand-Amundsen et al, 2018c), to predict intestinal tissue viability and histological grading based on the reference data (Strand-Amundsen et al, 2018a) indicates that good binary prediction of tissue viability is possible based on one bioimpedance measurement before reperfusion and an FNN model. When using the whole time-course of repeated bioimpedance measurement during the experiments a significantly higher accuracy was obtained by utilizing LSTM-RNN ( Figure 29).…”
Section: Machine Learning and Bioimpedance -Results (Paper V)mentioning
confidence: 99%
“…Prediction of tissue viability was assessed for different data points and segments, based on estimation of clinical application and relevance of the method. Classification using all or clinically relevant intervals of history of repeated measurements with different labels, was compared to classification using single measurement points at selected intervals, employing suitable machine learning approaches for both cases (Strand-Amundsen et al, 2018c).…”
Section: Machine Learning and Bioimpedance (Paper V)mentioning
confidence: 99%
See 1 more Smart Citation
“…While we do not aim to exhaustively assess the myriad of possibilities and methods within the realm of machine learning, we do intend to cast light on possibilities with neural network architectures for time-series data of bioimpedance. A recent study in our group compared the accuracy of using FNN, versus the accuracy when using LSTM-RNN with classification of intestinal viability following ischemia/reperfusion and found that accuracies in the range of what has been reported clinically can be achieved using FNN's on a single bioimpedance measurement, and higher accuracies can be achieved when employing LSTM-RNN on a sequence of data history (13).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies from our group demonstrated promising results using a recurrent neural network (RNN) with long short-term memory (LSTM). Through hours long measurements, they obtained high classification accuracies using repeated measurements in tissue related studies suggesting that this type of machine learning approach may be useful in a wider sense for impedance time series problems [16,17].…”
Section: Introductionmentioning
confidence: 99%